2013
DOI: 10.9775/kvfd.2012.7616
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Animal Species in Some Meat and Meat Products by Comparatively Using DNA Microarray and Real Time PCR Methods

Abstract: Determination of animal species in the meat and meat products is one of the interest of food science, it is also important for consumer rights and food safety. Increasing world population has also remarkably impacted the demand for meat and meat products. Based on this fact, issues related to safety and quality in the meat products have brought up in that manner as well. Through DNA based molecular methods are improved in food analysis, it is preferred increasingly in the control of food safety. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…However, previous market studies in Mexico, Turkey, and South Africa have reported mislabeling rates of approximately 20e70% for a variety of meat products, including sausage, ground meat, meat balls, deli meats, and dried meats (Ayaz, Ayaz, & Erol, 2006;Cawthorn, Steinman, & Hoffman, 2013;D'Amato, Alechine, Cloete, Davison, & Corach, 2013;Flores-Munguia, BermudezAlmada, & Vazquez-Moreno, 2000;Ozpinar, Tezmen, Gokce, & Tekiner, 2013). For example, a South African study testing processed meat products found that 68% of the samples contained species that were not declared on the package labels (Cawthorn et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…However, previous market studies in Mexico, Turkey, and South Africa have reported mislabeling rates of approximately 20e70% for a variety of meat products, including sausage, ground meat, meat balls, deli meats, and dried meats (Ayaz, Ayaz, & Erol, 2006;Cawthorn, Steinman, & Hoffman, 2013;D'Amato, Alechine, Cloete, Davison, & Corach, 2013;Flores-Munguia, BermudezAlmada, & Vazquez-Moreno, 2000;Ozpinar, Tezmen, Gokce, & Tekiner, 2013). For example, a South African study testing processed meat products found that 68% of the samples contained species that were not declared on the package labels (Cawthorn et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…Other studies have reported mislabeling rates of 20e70% for various meat products, including ground meat, deli meats, pet foods, and dried meats (Ayaz, Ayaz, & Erol, 2006;Cawthorn, Steinman, & Hoffman, 2013;Flores-Munguia, Bermudez-Almada, & Vazquez-Moreno, 2000;Mousavi et al, 2015;Okuma & Hellberg, 2015;Ozpinar, Tezmen, Gokce, & Tekiner, 2013;Pascoal, Prado, Castro, Cepeda, & Barros-Vel azquez, 2004;Quinto, Tinoco, & Hellberg, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Real time PCR has significant advantages over other methods [20,35] . On the other hand, success of a Real time PCR is dependent on a well-performed DNA extraction from test matrix [25,36] .…”
Section: Discussionmentioning
confidence: 99%